Numerical investigation of the flow inside primary zone of tubular combustor model - Eldrainy, Yehia A.; Mohd. Jaafar, Mohammad Nazri; Mat Lazim, Tholudin (Faculty of Mechanical Engineering, 2008)

(untitled)
In this study, a numerical simulation of non-reacting flow inside a gas turbine combustor model was performed. The main target of this investigation is to get physical insight of the main vortex, responsible for the efficient mixing of fuel and air. Such models are necessary for developing and optimization of real combustors. Combustor swirler assists the fuel-air mixing process by producing recirculation region which can act as flame holders as well. Therefore, proper selection of a swirler is needed to stabilize the flame, to enhance combustor performance and to reduce NOx emissions. For that reason, several axial swirlers with different configurations were employed to show their effects on primary zone aerodynamics performance. The three-dimensional, steady, turbulent and isothermal flow inside the combustor model was simulated using a finite volume based CFD code FLUENT 6.2. The combustor model geometry was created by means of solid model CAD software then the meshing was generated using GAMBIT preprocessing software subsequently, and the solution and the results analysis were carried out in a FLUENT solver. The effects of different swirlers’ configurations and inlet mass flow rate on flow dynamics were examined. A two recirculation zones were predicted, the first one is a central recirculation and located in the region immediately downstream of the swirler and the second is corner recirculation and located in the upstream corner of the combustion chamber. The results show that swirlers’ configuration and inlet mass flow rate have a significant effect on the combustor flowfield and pressure losses. By the mean that as swirl number increases the central recirculation zone size, turbulence production and pressure loss increase.